Інтерактивне навчання на уроках математики у початковій школі - Остапйовська, Ірина; Смаль, Оксана (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті коротко актуалізовано поняття «інтерактивні технології» специфіку їх реалізації в освітньому процесі, обґрунтовано доцільність їх використання в умовах нової української школи. Також авторами проаналізовано можливості їх використання на уроках математики у початковій школі, наведено приклади використання для навчання окремих тем та зразки можливих дидактичних матеріалів. Коротко окреслено перспективи подальших досліджень.The concept of «interactive technologies» as a type of educational technology were briefly actualized in the article. Briefly reviewed interactive technologies (interactive technology), such as: work in pairs, rotational (interchangeable) triples, work in small groups, interactive technologies of collective group learning («Microphone», «Unfinished sentences», «Brainstorming», «Learning – learn», «Openwork Saw», «Situation Analysis», «Problem Solving», «Decision Tree»), technology of situational modeling, as well as the specificity of their implementation in the educational process of an primary school, justified the expediency of their use in the new Ukrainian school. Also, the authors analyzed the possibilities of their use in the lessons of mathematics in primary school, provided examples of use for the study of certain topics and samples of possible didactic materials. The prospects for further research are briefly outlined.
Keywords: методика математики; інтерактивні технології; початкова школа; уроки математики у початковій школі